Albanian and English Hand in Hand Phraseologically (European Journal of Language and Literature, 2019)
Phraseological expressions which contain at least one body-part are common in all the languages. In this paper we want to compare those kinds of expressions which are formed with the word dorë/ duar in Albanian and hand in English. Our expressions are extracted both form monolingual and bilingual Albanian and English phraseological dictionaries. The expressions we have chosen are analysed from the cognitive standpoint, i.e. when we look at the expressions we try to gain an insight into how these two peoples, speaking languages which are distantly related and different in terms of organisation, see and conceptualize the world around them and as a result shape it linguistically. This process has undoubtedly attracted the attention of researchers (and the resulting ongoing debate) around the world. In order to see how comparable the world view and cultures of these two languages and peoples are we compare the syntactic and semantic structure of phraseological expressions containing the relevant body-part term.